Effective immobilization of Bacillus subtilis in chitosan-sodium alginate composite carrier for ammonia removal from anaerobically digested swine wastewater. (December 2021) - Guo, Junyuan; Chen, Cheng; Chen, Wenjing; Jiang, Jianying; Chen, Bozhi; Zheng, Fei
Abstract: To overcome the easy loss of microorganism, the mass production of sludge and the consumption of aeration energy during biological treatment of anaerobically digested swine wastewater, this study used chitosan–sodium alginate composite carrier to prepare immobilized bacteria pellets. The heterotrophic bacteria tolerant to high concentrations of ammonia nitrogen were isolated and the conditions for immobilizing bacteria were optimized. The performance of immobilized bacteria pellets to remove ammonia nitrogen from ADSW was determined and the corresponding mechanism was investigated. Results showed that the isolated bacteria were Bacillus subtilis, and the optimal conditions to prepare the immobilized bacteria pellets by response surface methodology tests were sodium alginate of 0.84% (m/V), chitosan of 0.22% (m/V), embedding time of 32 min and embedding amount of 15% (V/V). In ADSW treatment, at pH 6, 20 g/L of the immobilized bacteria pellets removed 96.5% of ammonia nitrogen. Both adsorption and microbial action contributed to ammonia nitrogen removal, and their contributions were 54.3% and 42.2%, respectively. Compared with the immobilized bacteria pellets using chitosan–sodium alginate as carrier, the one using mono alginate as carrier had a weaker ability to remove ammonia nitrogen, with a removal efficiency of 67.4%. The main mechanism was the formation of polyelectrolyte membrane by the connection between amino groups of chitosan and carboxyl groups of sodium alginate, which stabilized the immobilized bacteria pellets and prolonged their service life. To sum up, the immobilized bacteria pellets using chitosan–sodium alginate as an embedding agent have a promising prospect in ammonia nitrogen removal from wastewater. Graphical abstract: Image 1 Highlights: It is first time that chitosan-sodium alginate was used as embedding agent. Immobilization condition was optimized by the surface response methodology. Immobilized bacteria pellets removed 96.5% of ammonia nitrogen from ADSW. Microbial action and adsorption were the main mechanisms for ammonia removal.